Testing of design and functionality of front suspension arm in UNY automotive electric vehicle for individuals with disabilities - Candra Kusuma Aditama; Muhammad Yusri Ismail; Ibnu Siswanto (Journal of Automotive and Mechanical Applied Technology, 2025)
This study aims to evaluate the design and functionality of the front suspension arm in an electric vehicle specifically designed for users with disabilities. The research focuses on the lower arm component, analyzing its structural integrity through finite element analysis using ANSYS Student Version. The simulation was conducted under two loading conditions: 1300 N and 4800 N, representing different stress scenarios based on the vehicle's weight distribution. The safety factor analysis indicates that under a 1300 N load, the lower arm achieves a safety factor of 9.37, demonstrating high structural strength. Under an increased 4800 N load, the safety factor decreases to 2.54, which remains within the acceptable range (2.5–4.0) for static components subjected to dynamic loads. In terms of stress distribution, the simulation results indicate that the maximum stress is 39.51 MPa at a load of 1300 N. In contrast, it reaches 145.9 MPa at 4800 N. The displacement analysis reveals that the maximum deformation under 1300 N is 0.03023 mm, increasing to 0.1116 mm under 4800 N, indicating minimal structural deformation. Based on these findings, the lower arm suspension is deemed structurally safe and capable of withstanding the expected operational loads. These results offer valuable insights for the development of adaptive electric vehicles, ensuring their reliability and safety for users with disabilities.